2000
DOI: 10.1093/humrep/15.9.2052
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of donor insemination to the child: the impact of Swedish legislation on couples' attitudes

Abstract: The question whether or not parents of children conceived after donor insemination (DI) tell their offspring about its biological background was addressed. Swedish legislation from 1985 gives the child born after DI the right, when grown up, to receive identifying information about the sperm donor. Until now no information about compliance with the law has been available. All parents who gave birth to a child by DI after the new legislation in two major Swedish fertility centres (Stockholm and Umeâ) received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
1
15

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(118 citation statements)
references
References 22 publications
5
97
1
15
Order By: Relevance
“…The guidelines by the Swedish National Board of Health and Welfare stress that the physician, as a part of the psychosocial investigation, must ensure that the couple will tell their child about her/his genetic origin. However, a study from year 2000 of Swedish parents after donor insemination indicated poor compliance with these guidelines [8]. A slight majority had told (11%) or intended to tell (41%) their children about the donation, which is a necessary prerequisite for offspring to exercise their legal right to obtain identifiable information about the donor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The guidelines by the Swedish National Board of Health and Welfare stress that the physician, as a part of the psychosocial investigation, must ensure that the couple will tell their child about her/his genetic origin. However, a study from year 2000 of Swedish parents after donor insemination indicated poor compliance with these guidelines [8]. A slight majority had told (11%) or intended to tell (41%) their children about the donation, which is a necessary prerequisite for offspring to exercise their legal right to obtain identifiable information about the donor.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from the US [7], physicians were the only group of health professionals who encouraged or supported non-disclosure for couples who conceived using gamete donor treatment. Such types of behaviour among doctors involved in assisted reproduction may be related to the limited compliance with national legislation on disclosure among Swedish recipients of donor sperm [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted before removal of anonymity suggests that most children are ignorant of their donor offspring status [22][23][24][25]. Other European studies revealed that most couples did not intend to tell their children of their DI origins [26][27][28]. More recently, Golombok et al [25], in a study of 94 families with children conceived by DI, found that only 8.6% of DI children had been informed about their genetic origins, compared with 50% of in vitro fertilization (IVF) parents and 95% of adoptive parents.…”
Section: Rights Of the Childmentioning
confidence: 99%
“…However, the fact that semen volume and motility decrease continuously with age 42 (Eskenazi et a!., 2003), and that such sperm is less capable of fertilising an egg, makes older sperm donors less desirable in practice. Moreover, despite having a significant impact on the donor profile, the Swedish Act has not been successful in changing disclosure patterns (Gottlieb, Lalos and Lindblad, 2000;Lalos et a!., 2003).…”
Section: The Donor Shortagementioning
confidence: 99%
“…The research evidence identifies three main reasons for secrecy: first, that couples may view the decision not to disclose as protecting them from negative societal reactions, and preventing their child being considered different from others (Lalos, Gottlieb and Lalos, 2007;Nachtigall et al, 1997); second, that male partners may have concerns that the acknowledgement of infertility would cause their masculinity to come under suspicion (Courtenay, 2000;Glover et al, 1996;Miall, 1996;Nachtigall, Becker and Wozny, 1992); and third, that family relationships (particularly father-child) would be damaged if the child's real genetic identity was revealed (Gottlieb, Lalos and Lindblad, 2000;Lalos, Gottlieb and Lalos, 2007). I found that the users of Repromed express similar concerns.…”
mentioning
confidence: 99%